88% of consumers open to call centre voice biometrics. (April 2017) - Unknown
Abstract : Consumers in Asia Pacific are overwhelmingly in favour of companies using voice recognition to authenticate their identity when interacting with a contact centre. A NICE survey of 900 consumers in Australia, Hong Kong, India, Indonesia, Philippines and Singapore discovered the following: